2016
DOI: 10.1002/chem.201603002
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Polymers for Membrane CO2/N2 Separation

Abstract: This Concept examines strategies to design advanced polymers with high CO permeability and high CO /N selectivity, which are the key to the success of membrane technology for CO capture from fossil fuel-fired power plants. Specifically, polymers with enhanced CO solubility and thus CO /N selectivity are designed by incorporating CO -philic groups in polymers such as poly(ethylene oxide)-containing polymers and poly(ionic liquids); polymers with enhanced CO diffusivity and thus CO permeability are designed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 98 publications
3
90
0
Order By: Relevance
“…Owing to their excellent thermal and mechanical stability, structural tunability, and film‐forming ability, polymeric membranes have attracted considerable attention for various applications such as hydrogen recovery, O 2 enrichment, purification of natural gas, and so forth . The performance of membranes for gas separation applications is judged by permeability and selectivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their excellent thermal and mechanical stability, structural tunability, and film‐forming ability, polymeric membranes have attracted considerable attention for various applications such as hydrogen recovery, O 2 enrichment, purification of natural gas, and so forth . The performance of membranes for gas separation applications is judged by permeability and selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that polymers containing ionic groups exhibit excellent gas permeation properties and their gas permeation properties can be tuned by varying compositions of ionic groups . For CO 2 separation, polymers containing ionic groups showed high selectivity and high permeability because of interaction of ionic counterpart with CO 2 . To date, various examples of polymers containing ionic groups have been reported for gas separation applications including polybenzimidazoles, polyethers, polyimides, and so forth .…”
Section: Introductionmentioning
confidence: 99%
“…found that the substituent of PILs membrane as well as anion play important roles in governing gas diffusion and sorption, and thus the overall permeability. Liu et al . prepared the membranes with CO 2 ‐philic groups (poly(ethylene oxide)‐containing polymers and PILs) for CO 2 /N 2 Separation.…”
Section: Co2 Capture and Separation By Ionic Liquids‐based Membranesmentioning
confidence: 99%
“…Polymeric membranes are of great interests for removal of CO 2 from a mixture of light gases, such as CH 4 and N 2 , due to their inherently high‐energy efficiency in gas separation . For example, membrane technology is industrially practiced to remove CO 2 from natural gas (containing mainly CH 4 ) to avoid the corrosion of pipelines and has been extensively explored for CO 2 capture from post‐combustion flue gas derived from fossil fuels (containing mainly N 2 ) . These polymers selectively permeate CO 2 and reject CH 4 and N 2 based on the solution‐diffusion mechanism in which gas permeability ( P A ) of gas A is: PnormalA=SnormalA×DnormalA where, S A is the solubility coefficient and D A is the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%